Composite aramid paper and preparation method thereof

By introducing heterocyclic aramid nanofibers into para-aramid paper, the paper interface problems and dispersion problems are solved, and the mechanical properties and electrical insulation properties are improved, making them suitable for high-performance applications.

CN119640610APending Publication Date: 2025-03-18TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202510052361.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing para-aramid paper has interface problems and dispersion problems during papermaking, resulting in poor mechanical strength of paper and low internal bonding strength, which limits its development in high-performance applications.

Method used

By introducing heterocyclic aramid nanofibers, the interfacial adhesion problem of para-aramid paper is improved, and the high specific surface area and strong intermolecular force of heterocyclic aramid nanofibers are used to enhance the bonding force between the fibers and improve the mechanical properties and electrical insulation of the paper.

Benefits of technology

It significantly improves the mechanical properties, internal bonding strength and electrical insulation properties of aramid paper, forming a denser and even paper structure, suitable for high-end insulated paper and aramid paper honeycomb industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640610A_ABST
    Figure CN119640610A_ABST
Patent Text Reader

Abstract

The invention provides composite aramid paper and a preparation method thereof. The preparation method comprises the following steps: preparation of a heterocyclic aramid stock solution: mixing p-phenylenediamine, a diamine monomer containing a heterocyclic structure and terephthaloyl chloride in a solvent for polymerization to obtain the heterocyclic aramid stock solution; preparing heterocyclic aramid nanofibers: diluting the heterocyclic aramid stock solution with a solvent, mixing the diluted heterocyclic aramid stock solution with a poor solvent, stirring, shearing, dispersing, and cleaning to obtain the heterocyclic aramid nanofibers; preparation of mixed slurry: mixing and pulping para-aramid and the heterocyclic aramid nanofiber to obtain the mixed slurry; and papermaking of the composite aramid paper: performing papermaking on the mixed pulp to obtain the composite aramid paper. And papermaking of the composite aramid paper: performing papermaking on the mixed pulp to obtain the composite aramid paper. According to the method, the heterocyclic aramid nanofiber is introduced into the para-aramid paper, so that the interface bonding problem of the para-aramid paper can be improved, and the internal bonding strength, the mechanical property and the electrical insulating property of the para-aramid paper are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite aramid paper and a preparation method thereof, in particular to a para-aramid paper reinforced with heterocyclic aramid nanofibers and a preparation method thereof, belonging to the technical field of aramid paper. Background Art

[0002] As a polymer paper-based material, aramid paper has excellent mechanical properties, chemical and thermal stability, and electrical insulation properties. It can be used as a structural material to prepare aramid paper honeycombs and laminates, and applied to rigid load-bearing structural components of aircraft, high-speed railways, ships, etc., or as an insulating material in transformers, motors, and electric motors. It can also be used as a diaphragm, thermal protection and other fields.

[0003] In current industrial production, para-aramid paper is typically made from a mixture of chopped fibers and pulp in a specific ratio using a wet-laid forming and hot-pressing process. The chopped fibers have a smooth surface and are chemically inert, which can lead to interface and dispersion issues during the papermaking process. This poor interfacial adhesion between the chopped fibers and pulp results in a loose bond, large pores, and numerous defects. This results in poor mechanical strength and low internal bonding strength, significantly limiting the development of para-aramid paper in high-performance applications.

[0004] Introducing nano-based materials into the para-aramid papermaking process is an effective way to improve its structure and properties, because nanofibers generally have high specific surface area and nanoscale enhancement effect.

[0005] Reference 1 provides an aramid fiber-plant nanofiber composite aramid paper and its preparation method. This method improves the surface bonding and dispersion of the aramid fibers by introducing plant nanofibers as a third adhesive fiber. However, the introduction of this third adhesive fiber reduces the temperature resistance of the finished paper.

[0006] Reference 2 provides a para-aramid paper reinforced with aramid nanofibers and a method for preparing the same. The introduction of para-aramid nanofibers in this method improves the mechanical and insulating properties of the para-aramid. However, since the nanofibers are prepared by deprotonation and then reduction, the improvement in the paper quality is limited.

[0007] It can be seen that although a series of studies have been conducted in this field on improving the performance of para-aramid paper, the research on improvement methods for interface problems and dispersion problems cannot be said to be sufficient, and the internal bonding strength of the finished paper is relatively low, and there is still room for further improvement.

[0008] References:

[0009] Reference 1: CN112553959A

[0010] Reference 2: CN108265566A Summary of the Invention

[0011] Problems to be solved by the invention

[0012] In view of the above situation, the present invention provides a method for preparing a composite aramid paper obtained by reinforcing para-aramid paper with heterocyclic aramid nanofibers. Heterocyclic aramid is an aramid material prepared by introducing a third monomer into the molecular structure of para-aramid. The introduction of the third monomer can improve the flexibility of the aramid chain segments and the intermolecular effect, and improve the crystallization performance of the aramid. Therefore, the heterocyclic aramid has good mechanical properties and thermal stability. The heterocyclic aramid is further processed into heterocyclic aramid nanofibers. The heterocyclic aramid nanofibers can not only maintain the excellent performance of heterocyclic aramid, but also have extremely strong intermolecular interactions and film-forming properties. In this method, by introducing heterocyclic aramid nanofibers into para-aramid paper, the interfacial bonding problem of para-aramid paper can be effectively improved, thereby greatly improving the comprehensive performance of the aramid paper, such as mechanical properties, internal bonding strength and electrical insulation.

[0013] The present invention also provides a composite aramid paper, which is obtained by the preparation method of the present invention. The composite aramid paper of the present invention has excellent mechanical properties, uniformity, internal bonding strength and electrical insulation properties.

[0014] Solutions for solving problems

[0015] The present invention first provides a method for preparing composite aramid paper, which comprises the following steps:

[0016] Preparation of heterocyclic aramid stock solution: p-phenylenediamine, a diamine monomer containing a heterocyclic structure and terephthaloyl chloride are mixed in a solvent and polymerized to obtain a heterocyclic aramid stock solution;

[0017] Preparation of heterocyclic aramid nanofibers: diluting the heterocyclic aramid stock solution with a solvent, mixing it with a poor solvent, stirring, shearing, dispersing, and washing to obtain heterocyclic aramid nanofibers;

[0018] Preparation of mixed slurry: mixing para-aramid and the heterocyclic aramid nanofibers and beating them to obtain mixed slurry;

[0019] Papermaking of composite aramid paper: papermaking the mixed slurry to obtain composite aramid paper.

[0020] According to the preparation method of the present invention, the diamine monomer containing a heterocyclic structure includes 2-(4-aminophenyl)-5-aminobenzimidazole.

[0021] According to the preparation method of the present invention, the ratio of the total molar amount of the p-phenylenediamine and the diamine monomer containing a heterocyclic structure to the molar amount of the terephthaloyl chloride is 1:1.001 to 1:1.007; and / or,

[0022] The molar ratio of the p-phenylenediamine to the diamine monomer containing a heterocyclic structure is 3:7 to 8:2; and / or,

[0023] The molar concentration of the terephthaloyl chloride is 0.1-0.3 mol / L.

[0024] According to the preparation method of the present invention, in the preparation of the heterocyclic aramid stock solution and the preparation of the heterocyclic aramid nanofibers, the solvent includes one or more of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone.

[0025] According to the preparation method of the present invention, the heterocyclic aramid stock solution further includes a cosolvent, and the cosolvent includes one or more of lithium chloride, calcium chloride, lithium bromide or calcium bromide;

[0026] Preferably, the amount of the co-solvent added is 2-10% of the mass of the solvent.

[0027] According to the preparation method of the present invention, wherein, in the preparation of the heterocyclic aramid nanofibers, the solvent is diluted by 5 to 20 times; and / or,

[0028] The poor solvent includes one or more of water, methanol, ethanol, and tert-butanol.

[0029] According to the preparation method of the present invention, in the preparation of the mixed slurry, the basis weight of the paper is 20 to 150 g / m 2 and / or,

[0030] The amount of the heterocyclic aramid nanofiber added is 20 to 150% of the total mass of the para-aramid; and / or,

[0031] The para-aramid fiber includes para-aramid short fibers and para-aramid pulp;

[0032] Preferably, the mass ratio of the para-aramid chopped fibers to the para-aramid pulp is 3:7 to 7:3.

[0033] According to the preparation method of the present invention, the mixed slurry further includes a dispersant, and the dispersant includes one or more of polyethylene oxide, polyacrylamide, and sodium alginate;

[0034] Preferably, the added amount of the dispersant is 0.01 to 1% of the total mass of the para-aramid.

[0035] According to the preparation method of the present invention, the papermaking includes dehydration, drying and shaping, and high-temperature calendering treatment;

[0036] Preferably, the dehydration comprises wire dehydration and press dehydration; and / or,

[0037] The drying temperature is 60-200° C. and the drying time is 3-60 min; and / or,

[0038] The temperature of the high-temperature calendering treatment is 100-200° C., the pressure of the high-temperature calendering treatment is 3-10 MPa, and the time of the high-temperature calendering treatment is 1-10 minutes.

[0039] In addition, the present invention also provides a composite aramid paper, wherein the composite aramid paper is prepared by the preparation method according to the present invention.

[0040] Effects of the Invention

[0041] The preparation method of the composite aramid paper provided by the present invention introduces heterocyclic aramid nanofibers into para-aramid paper during the papermaking process, fully utilizing the advantages of the heterocyclic aramid nanofibers, such as high specific surface area, excellent mechanical properties, abundant hydrogen bonding, strong intermolecular forces, and extremely strong film-forming properties. During papermaking and molding, the microstructure of the aramid paper can be greatly improved, the porosity and defects of the aramid paper can be reduced, the adhesion between the aramid short fibers and the aramid pulp can be enhanced, and the interfacial adhesion problem of the para-aramid paper can be effectively improved, thereby greatly improving the comprehensive properties of the aramid paper, such as mechanical properties, internal bonding strength, and electrical insulation.

[0042] The composite aramid paper of the present invention has excellent mechanical properties, internal bonding strength, uniformity and electrical insulation properties, and can be applied to industries such as high-end insulating paper and aramid paper honeycomb that have high requirements on paper properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A photo of the composite aramid paper prepared in the present invention is shown. DETAILED DESCRIPTION

[0044] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The word "exemplary" is used herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior or preferred over other embodiments.

[0045] In addition, numerous specific details are provided in the following detailed description to better illustrate the present invention. Those skilled in the art will appreciate that the present invention can be practiced without certain specific details. In other instances, methods, means, equipment, and steps well known to those skilled in the art are not described in detail in order to highlight the main points of the present invention.

[0046] Unless otherwise stated, the units used in this specification are international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0047] In this specification, the use of "may" includes both the meaning of performing a certain process and the meaning of not performing a certain process.

[0048] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "embodiments," etc., mean that the specific elements (e.g., features, structures, properties, and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not be present in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0049] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.

[0050] <First Aspect>

[0051] A first aspect of the present invention provides a method for preparing a composite aramid paper, comprising the following steps:

[0052] Preparation of heterocyclic aramid stock solution: p-phenylenediamine, a diamine monomer containing a heterocyclic structure and terephthaloyl chloride are mixed in a solvent and polymerized to obtain a heterocyclic aramid stock solution;

[0053] Preparation of heterocyclic aramid nanofibers: diluting the heterocyclic aramid stock solution with a solvent, mixing it with a poor solvent, stirring, shearing, dispersing, and washing to obtain heterocyclic aramid nanofibers;

[0054] Preparation of mixed slurry: mixing para-aramid and the heterocyclic aramid nanofibers and beating them to obtain mixed slurry;

[0055] Papermaking of composite aramid paper: papermaking the mixed slurry to obtain composite aramid paper.

[0056] Preparation of heterocyclic aramid stock solution

[0057] In the present invention, the heterocyclic aramid stock solution is prepared by mixing p-phenylenediamine, a diamine monomer containing a heterocyclic structure, and terephthaloyl chloride in a solvent and polymerizing the mixture to obtain the heterocyclic aramid stock solution. By copolymerizing the heterocyclic diamine monomer with p-phenylenediamine and terephthaloyl chloride, the heterocyclic structure can be introduced into the main chain of the para-aramid to obtain the heterocyclic aramid.

[0058] In principle, there is no particular limitation on the type of the heterocyclic diamine monomer. Benzimidazole ring-containing diamine monomers commonly used in the preparation of heterocyclic aramids in the art can be used. In some specific embodiments, the heterocyclic diamine monomer can include 2-(4-aminophenyl)-5-aminobenzimidazole, etc.

[0059] In principle, there is no particular limitation on the type of the solvent, and the solvent can be selected as needed. In some specific embodiments, the solvent can include one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, and the like.

[0060] In some specific embodiments, in order to further promote the reaction, a cosolvent may be added during the preparation of the heterocyclic aramid stock solution. There is no particular limitation on the method of adding the cosolvent, which may be added to the solvent simultaneously with the reaction monomers.

[0061] As for the type of the co-solvent, in some specific embodiments, it can include one or more of lithium chloride, calcium chloride, lithium bromide or calcium bromide.

[0062] The dosage of each substance in the preparation process of heterocyclic aramid stock solution can be set according to the following dosage in order to improve the comprehensive performance of composite aramid:

[0063] The ratio of the total molar amount of the p-phenylenediamine and the diamine monomer containing a heterocyclic structure to the molar amount of the terephthaloyl chloride is 1:1.001 to 1:1.007, for example, 1:1.002, 1:1.003, 1:1.004, 1:1.005, 1:1.006, etc.

[0064] The molar ratio of the p-phenylenediamine to the diamine monomer containing a heterocyclic structure is 3:7 to 8:2, for example, 4:6, 5:5, 6:4, 7:3, etc.

[0065] The molar concentration of the terephthaloyl chloride is 0.1 to 0.3 mol / L, for example, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, etc.

[0066] The amount of the co-solvent added is 2-10% of the mass of the solvent, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc.

[0067] Preparation of heterocyclic aramid nanofibers

[0068] In the present invention, the heterocyclic aramid nanofibers are prepared by diluting the heterocyclic aramid stock solution obtained above with a solvent, mixing it with a poor solvent, and stirring, shearing, dispersing, and washing it to obtain the heterocyclic aramid nanofibers.

[0069] Specifically, the preparation of the heterocyclic aramid nanofiber includes: diluting the heterocyclic aramid stock solution obtained above with a solvent used for polymerization in a certain proportion to obtain a dilution solution; then slowly adding the dilution solution into a poor solvent for heterocyclic aramid, and simultaneously performing high-speed shear dispersion to obtain a heterocyclic aramid nanofiber dispersion solution; and thoroughly washing the heterocyclic aramid nanofiber dispersion solution with deionized water to obtain the heterocyclic aramid nanofiber.

[0070] In some specific embodiments, the dilution multiple can be 5 to 20 times, for example, 8 times, 10 times, 12 times, 15 times, 18 times, etc.

[0071] The present invention does not specifically limit the type of the poor solvent, and the poor solvent can be selected as needed. In some specific embodiments, the poor solvent can include one or more of water, methanol, ethanol, and tert-butanol.

[0072] The present invention does not impose any particular limitation on the shear rate, as long as the heterocyclic aramid nanofibers can be sufficiently and evenly dispersed in the poor solvent. In some specific embodiments, the shear rate can be 1000-2000 rpm, for example, 1200 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1800 rpm, etc.

[0073] Preparation of mixed slurry

[0074] In the present invention, the mixed slurry is prepared by mixing the para-aramid and the heterocyclic aramid nanofibers obtained above and beating the mixture to obtain the mixed slurry.

[0075] In some specific embodiments, the basis weight of the paper can be 20 to 150 g / m 2 , for example, it can be 40g / m 2 , 60g / m 2 , 80g / m 2 , 100g / m 2 , 120g / m 2 , 140g / m 2 wait.

[0076] In some specific embodiments, the para-aramid fiber comprises para-aramid short fibers and para-aramid pulp, wherein the mass ratio of the para-aramid short fibers to the para-aramid pulp is 3:7 to 7:3, for example, 4:6, 5:5, 6:4, etc.

[0077] In some specific embodiments, the amount of heterocyclic aramid nanofibers added is 20-150% of the total mass of the para-aramid, for example, 40%, 60%, 80%, 100%, 120%, 140%, etc. When the amount of heterocyclic aramid nanofibers added is less than 20% of the total mass of the para-aramid, the reinforcing effect on the aramid paper is poor. When the amount of heterocyclic aramid nanofibers added is greater than 150% of the total mass of the para-aramid, on the one hand, the aramid paper may be too dense, resulting in a small amount of aramid paper impregnation, which is not conducive to the bonding of paper honeycombs and, therefore, is not conducive to the preparation of aramid paper honeycombs. On the other hand, during the papermaking process, the heterocyclic aramid nanofibers may be deposited in the lower layer due to the excessive content, ultimately resulting in uneven front and back surfaces of the aramid paper.

[0078] By mixing and beating heterocyclic aramid nanofibers, para-aramid short fibers and para-aramid pulp in the above-mentioned proportions and carrying out papermaking as described later, the advantages of each component in aramid paper can be fully utilized. Para-aramid short fibers serve as a skeleton support to provide mechanical properties of the paper. Para-aramid pulp acts as a binder to improve the uniformity and toughness of the finished paper. Heterocyclic aramid nanofibers fill and adhere to the gaps between the short fibers and the aramid pulp, filling the pores therein and linking the two more closely, so that the para-aramid short fibers, para-aramid pulp and heterocyclic aramid nanofibers in the paper form a "brick-sand-cement" structure in concrete, thereby improving the mechanical strength and internal bonding strength of the aramid paper.

[0079] In some specific embodiments, in order to further improve the dispersion effect of the components in the slurry, a dispersant may be added during the preparation of the mixed slurry. The type of the dispersant is not particularly limited and may be selected as needed. For example, it may include one or more of polyethylene oxide, polyacrylamide, and sodium alginate.

[0080] In some specific embodiments, the added amount of the dispersant can be 0.01-1% of the total mass of the para-aramid, for example, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, etc.

[0081] Production of composite aramid paper

[0082] In the present invention, the composite aramid paper is prepared by papermaking the mixed slurry obtained above to obtain the composite aramid paper.

[0083] In some specific embodiments, the papermaking process includes dehydration, drying and shaping, and high-temperature calendering. Specifically, the papermaking process includes: (1) dehydrating the mixed slurry obtained above to obtain wet paper; (2) drying and shaping the dehydrated wet paper to obtain a primary paper product; and (3) subjecting the primary paper product to a high-temperature calendering process to obtain a finished composite aramid paper product.

[0084] The dehydration step is not particularly limited and can refer to dehydration steps commonly used in the art. In some specific embodiments, the dehydration includes wire dehydration and press dehydration. Specifically, a 50-400 mesh forming wire is selected to perform wire dehydration on the mixed slurry, thereby removing most of the water in the paper. Subsequently, 2-5 double-roll pressing methods are selected to perform press dehydration to further remove water from the paper to obtain wet paper.

[0085] The drying and shaping step is not particularly limited and can refer to the drying and shaping steps commonly used in the art. In some specific embodiments, the drying step includes drying and shaping the wet paper using a multi-cylinder drying technology, with a drying temperature of 60 to 200° C. and a drying time of 3 to 60 minutes.

[0086] The high-temperature calendering treatment step is not particularly limited and can refer to commonly used high-temperature calendering treatment steps in the art. In some specific embodiments, the high-temperature calendering treatment includes high-temperature calendering treatment at a pressure of 3 to 10 MPa and a temperature of 100 to 200° C. for 1 to 10 minutes to obtain a finished composite aramid paper.

[0087] <Second Aspect>

[0088] A second aspect of the present invention provides a composite aramid paper, which is obtained by the preparation method provided by the first aspect.

[0089] Example

[0090] The embodiments of the present invention will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the invention. Where specific conditions are not specified in the examples, the methods were performed according to conventional conditions or the conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be obtained commercially.

[0091] Example 1

[0092] Step (1): p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, terephthaloyl chloride and lithium chloride are mixed in N,N-dimethylacetamide and polymerized to obtain a heterocyclic aramid stock solution, wherein the ratio of the total molar amount of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to the molar amount of terephthaloyl chloride is 1:1.001, the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 3:7, the molar concentration of terephthaloyl chloride is 0.1 mol / L, and the amount of lithium chloride added is 3.5% of the mass of N,N-dimethylacetamide.

[0093] Step (2): diluting the heterocyclic aramid stock solution 5 times with N,N-dimethylacetamide to obtain a dilution solution, then slowly adding the dilution solution into water, and simultaneously performing high-speed shear dispersion at a rate of 1000 rpm to obtain a heterocyclic aramid nanofiber dispersion solution, and thoroughly washing the heterocyclic aramid nanofiber dispersion solution with deionized water to obtain heterocyclic aramid nanofibers.

[0094] Step (3) is to mix the para-aramid short fibers, para-aramid pulp, heterocyclic aramid nanofibers and polyethylene oxide and mechanically stir them to obtain a mixed slurry, wherein the paper basis weight is 20 g / m 2 The weight ratio of para-aramid short fibers to para-aramid pulp is 3:7, the heterocyclic aramid nanofiber content is 20% of the total weight of the para-aramid short fibers and para-aramid pulp, and the amount of polyethylene oxide added is 0.01% of the total weight of the para-aramid short fibers and para-aramid pulp.

[0095] In step (4), a 50-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a two-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 60° C. for 60 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 3 MPa and 200° C. for 10 minutes to obtain a finished composite aramid paper product.

[0096] Example 2

[0097] Step (1): p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, terephthaloyl chloride and calcium chloride are mixed in N,N-dimethylformamide and polymerized to obtain a heterocyclic aramid stock solution, wherein the ratio of the total molar amount of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to the molar amount of terephthaloyl chloride is 1:1.007, the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 8:2, the molar concentration of terephthaloyl chloride is 0.3 mol / L, and the amount of calcium chloride added is 10% by mass of N,N-dimethylformamide.

[0098] Step (2): diluting the heterocyclic aramid stock solution 20 times with N,N-dimethylformamide to obtain a dilution solution, then slowly adding the dilution solution into ethanol, and simultaneously performing high-speed shear dispersion at a rate of 2000 rpm to obtain a heterocyclic aramid nanofiber dispersion solution, and thoroughly washing the heterocyclic aramid nanofiber dispersion solution with deionized water to obtain heterocyclic aramid nanofibers.

[0099] Step (3), para-aramid short fibers, para-aramid pulp, heterocyclic aramid nanofibers, and polyacrylamide are mixed and mechanically stirred to obtain a mixed slurry, wherein the paper weight is 120 g / m 2 The mass ratio of para-aramid short fibers to para-aramid pulp is 7:3, the heterocyclic aramid nanofiber content is 150% of the total mass of the para-aramid short fibers and para-aramid pulp, and the amount of polyacrylamide added is 1% of the total mass of the para-aramid short fibers and para-aramid pulp.

[0100] In step (4), a 400-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a 5-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 200° C. for 3 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 10 MPa and 100° C. for 1 minute to obtain a finished composite aramid paper product.

[0101] Example 3

[0102] Step (1): p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, terephthaloyl chloride and calcium bromide are mixed in N-methylpyrrolidone and polymerized to obtain a heterocyclic aramid stock solution, wherein the ratio of the total molar amount of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to the molar amount of terephthaloyl chloride is 1:1.003, the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 5:5, the molar concentration of terephthaloyl chloride is 0.15 mol / L, and the amount of calcium bromide added is 5% by mass of N-methylpyrrolidone.

[0103] Step (2): diluting the heterocyclic aramid stock solution 10 times with N-methylpyrrolidone to obtain a dilution solution, then slowly adding the dilution solution into methanol, and performing high-speed shear dispersion at a rate of 1500 rpm to obtain a heterocyclic aramid nanofiber dispersion solution, and thoroughly washing the heterocyclic aramid nanofiber dispersion solution with deionized water to obtain heterocyclic aramid nanofibers.

[0104] Step (3), para-aramid short fibers, para-aramid pulp, heterocyclic aramid nanofibers, and sodium alginate are mixed and mechanically stirred to obtain a mixed slurry, wherein the paper weight is 60 g / m 2The weight ratio of para-aramid short fibers to para-aramid pulp is 5:5, the heterocyclic aramid nanofiber content is 80% of the total weight of the para-aramid short fibers and para-aramid pulp, and the amount of sodium alginate added is 0.5% of the total weight of the para-aramid short fibers and para-aramid pulp.

[0105] In step (4), a 200-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a three-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 100° C. for 10 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 5 MPa and 120° C. for 3 minutes to obtain a finished composite aramid paper product.

[0106] Example 4

[0107] Step (1): p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, terephthaloyl chloride and lithium bromide are mixed in N,N-dimethylacetamide and polymerized to obtain a heterocyclic aramid stock solution, wherein the ratio of the total molar amount of p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to the molar amount of terephthaloyl chloride is 1:1.005, the molar ratio of p-phenylenediamine to 2-(4-aminophenyl)-5-aminobenzimidazole is 6:4, the molar concentration of terephthaloyl chloride is 0.2 mol / L, and the amount of calcium bromide added is 8% by mass of N,N-dimethylacetamide.

[0108] Step (2): diluting the heterocyclic aramid stock solution 8 times with N, N-dimethylacetamide to obtain a dilution solution, then slowly adding the dilution solution into methanol, and simultaneously performing high-speed shear dispersion at a rate of 1800 rpm to obtain a heterocyclic aramid nanofiber dispersion solution, and thoroughly washing the heterocyclic aramid nanofiber dispersion solution with deionized water to obtain heterocyclic aramid nanofibers.

[0109] Step (3) is to mix the para-aramid short fibers, para-aramid pulp, heterocyclic aramid nanofibers and polyethylene oxide and mechanically stir them to obtain a mixed slurry, wherein the paper basis weight is 90 g / m 2 The mass ratio of para-aramid short fibers to para-aramid pulp is 6:4, the heterocyclic aramid nanofiber content is 100% of the total mass of the para-aramid short fibers and para-aramid pulp, and the amount of polyethylene oxide added is 0.8% of the total mass of the para-aramid short fibers and para-aramid pulp.

[0110] In step (4), a 300-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a four-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 150° C. for 30 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 8 MPa and 150° C. for 6 minutes to obtain a finished composite aramid paper product.

[0111] Comparative Example 1

[0112] The difference from Example 1 is that the heterocyclic aramid nanofibers are replaced with para-aramid nanofibers, specifically including:

[0113] In step (1), p-phenylenediamine, terephthaloyl chloride and lithium chloride are mixed in N,N-dimethylacetamide and polymerized to obtain a p-aramid stock solution, wherein the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1.001, the molar concentration of terephthaloyl chloride is 0.1 mol / L, and the amount of lithium chloride added is 3.5% by mass of N,N-dimethylacetamide.

[0114] Step (2): diluting the para-aramid stock solution 5 times with N,N-dimethylacetamide to obtain a dilution solution, then slowly adding the dilution solution into water, and simultaneously performing high-speed shear dispersion at a rate of 1000 rpm to obtain a para-aramid nanofiber dispersion solution, and thoroughly washing the para-aramid nanofiber dispersion solution with deionized water to obtain para-aramid nanofibers.

[0115] Step (3), para-aramid short fibers, para-aramid pulp, para-aramid nanofibers, and polyethylene oxide are mixed and mechanically stirred to obtain a mixed slurry, wherein the paper basis weight is 20 g / m 2 The mass ratio of para-aramid short fibers to para-aramid pulp is 3:7, the para-aramid nanofiber content is 20% of the total mass of the para-aramid short fibers and para-aramid pulp, and the amount of polyethylene oxide added is 0.01% of the total mass of the para-aramid short fibers and para-aramid pulp.

[0116] In step (4), a 50-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a two-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 60° C. for 60 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 3 MPa and 200° C. for 10 minutes to obtain a finished aramid paper product.

[0117] Comparative Example 2

[0118] The difference from Example 1 is that no heterocyclic aramid nanofibers are added to the papermaking components.

[0119] Comparative Example 3

[0120] The difference from Example 2 is that the heterocyclic aramid nanofibers are replaced with para-aramid nanofibers. Specifically, the following are included:

[0121] Step (1) is to mix p-phenylenediamine, terephthaloyl chloride and calcium chloride in N,N-dimethylformamide and polymerize them to obtain a p-aramid stock solution, wherein the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1.007, the molar concentration of terephthaloyl chloride is 0.3 mol / L, and the amount of calcium chloride added is 10% by mass of N,N-dimethylformamide.

[0122] Step (2): diluting the para-aramid stock solution 20 times with N,N-dimethylformamide to obtain a dilution solution, then slowly adding the dilution solution into ethanol, and simultaneously performing high-speed shear dispersion at a rate of 2000 rpm to obtain a para-aramid nanofiber dispersion solution, and thoroughly washing the para-aramid nanofiber dispersion solution with deionized water to obtain para-aramid nanofibers.

[0123] Step (3), para-aramid short fibers, para-aramid pulp, para-aramid nanofibers, and polyacrylamide are mixed and mechanically stirred to obtain a mixed slurry, wherein the paper weight is 120 g / m 2 The mass ratio of para-aramid short fibers to para-aramid pulp is 7:3, the para-aramid nanofiber content is 150% of the total mass of the para-aramid short fibers and para-aramid pulp, and the amount of polyacrylamide added is 1% of the total mass of the para-aramid short fibers and para-aramid pulp.

[0124] In step (4), a 400-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a 5-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 200° C. for 3 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 10 MPa and 100° C. for 1 minute to obtain a finished aramid paper product.

[0125] Comparative Example 4

[0126] The difference from Example 2 is that no heterocyclic aramid nanofibers are added to the papermaking components.

[0127] Comparative Example 5

[0128] The difference from Example 3 is that the heterocyclic aramid nanofibers are replaced with para-aramid nanofibers. Specifically, the following are included:

[0129] Step (1) is to mix p-phenylenediamine, terephthaloyl chloride and calcium bromide in N-methylpyrrolidone and polymerize them to obtain a p-aramid stock solution, wherein the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1.003, the molar concentration of terephthaloyl chloride is 0.15 mol / L, and the amount of calcium bromide added is 5% by mass of N-methylpyrrolidone.

[0130] Step (2): diluting the para-aramid stock solution 10 times with N-methylpyrrolidone to obtain a dilution solution, then slowly adding the dilution solution into methanol, and simultaneously performing high-speed shear dispersion at a rate of 1500 rpm to obtain a para-aramid nanofiber dispersion solution, and thoroughly washing the para-aramid nanofiber dispersion solution with deionized water to obtain para-aramid nanofibers.

[0131] Step (3), para-aramid short fibers, para-aramid pulp, para-aramid nanofibers, and sodium alginate are mixed and mechanically stirred to obtain a mixed slurry, wherein the paper weight is 60 g / m 2 The mass ratio of para-aramid short fibers to para-aramid pulp is 5:5, the para-aramid nanofiber content is 80% of the total mass of the para-aramid short fibers and para-aramid pulp, and the amount of sodium alginate added is 0.5% of the total mass of the para-aramid short fibers and para-aramid pulp.

[0132] In step (4), a 200-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a three-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 100° C. for 10 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 5 MPa and 120° C. for 3 minutes to obtain a finished aramid paper product.

[0133] Comparative Example 6

[0134] The difference from Example 3 is that no heterocyclic aramid nanofibers are added to the papermaking components.

[0135] Comparative Example 7

[0136] The difference from Example 4 is that the heterocyclic aramid nanofibers are replaced with para-aramid nanofibers. Specifically, the following are included:

[0137] In step (1), p-phenylenediamine, terephthaloyl chloride and lithium bromide are mixed in N,N-dimethylacetamide and polymerized to obtain a p-aramid stock solution, wherein the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1.005, the molar concentration of terephthaloyl chloride is 0.2 mol / L, and the amount of calcium bromide added is 8% by mass of N,N-dimethylacetamide.

[0138] Step (2): diluting the para-aramid stock solution 8 times with N,N-dimethylacetamide to obtain a dilution solution, then slowly adding the dilution solution into methanol, and simultaneously performing high-speed shear dispersion at a rate of 1800 rpm to obtain a para-aramid nanofiber dispersion solution, and thoroughly washing the para-aramid nanofiber dispersion solution with deionized water to obtain para-aramid nanofibers.

[0139] Step (3) is to mix the para-aramid short fibers, para-aramid pulp, para-aramid nanofibers and polyethylene oxide and mechanically stir them to obtain a mixed slurry, wherein the paper basis weight is 90 g / m 2 The mass ratio of para-aramid short fibers to para-aramid pulp is 6:4, the para-aramid nanofiber content is 100% of the total mass of the para-aramid short fibers and para-aramid pulp, and the amount of polyethylene oxide added is 0.8% of the total mass of the para-aramid short fibers and para-aramid pulp.

[0140] In step (4), a 300-mesh forming wire is selected to dehydrate the mixed slurry on the wire part, and then a four-pass double-roll pressing method is selected to press and dehydrate the mixed slurry to obtain wet paper. The wet paper is dried at 150° C. for 30 minutes using a multi-cylinder drying technology to obtain a primary paper product. The primary paper product is then subjected to a high-temperature calendering treatment at 8 MPa and 150° C. for 6 minutes to obtain a finished composite aramid paper product.

[0141] Comparative Example 8

[0142] The difference from Example 3 is that no heterocyclic aramid nanofibers are added to the papermaking components.

[0143] Performance Testing

[0144] 1. Thickness: The thickness of the aramid paper products obtained in Examples 1 to 4 and Comparative Examples 1 to 8 was measured using a spiral electronic thickness gauge.

[0145] 2. Tensile strength and internal bonding strength: The internal bonding strength and tensile strength of the aramid paper products obtained in Examples 1 to 4 and Comparative Examples 1 to 8 were tested using a universal tensile testing machine.

[0146] The specific test method for tensile strength is: cut the paper into standard samples and test the tensile strength of the paper using a universal tensile testing machine at a tensile rate of 5 mm / min. The test results are shown in Table 1.

[0147] The internal bonding strength was tested according to Method 1 in the standard GB / T 26203-2023. The test results are shown in Table 1.

[0148] 3. Electrical Insulation Performance: The electrical breakdown strength of the aramid paper products obtained in Examples 1-4 and Comparative Examples 1-8 was tested using a voltage breakdown tester. The specific testing method was as follows: the aramid paper was placed on the sample stage of the high-voltage breakdown tester, power was applied, and the electrical breakdown strength was measured after the paper broke down. The test results are shown in Table 1.

[0149] Table 1 Performance test results of the embodiments and comparative examples

[0150]

[0151] As shown in Table 1, it can be seen from the comparison between Examples 1 to 4 and Comparative Examples 1 to 8 that the present invention can significantly improve the mechanical properties, internal bonding strength and electrical insulation properties of aramid paper by introducing heterocyclic aramid nanofibers into para-aramid, and the aramid paper introduced with heterocyclic aramid nanofibers is better than the para-aramid paper introduced with para-aramid nanofibers, which illustrates the key role of heterocyclic aramid nanofibers in reinforcing aramid paper.

[0152] The present invention processes heterocyclic aramid into heterocyclic aramid nanofibers and introduces them into the papermaking process of aramid paper. The heterocyclic aramid nanofibers utilize their high specific surface area and abundant hydrogen bond interactions to have extremely strong film-forming properties. During the papermaking process, the interactions between fibers can be enhanced, the bonding force between fibers can be greatly improved, and the paper can be made denser and more uniform, thereby further significantly improving the tensile strength, internal bonding strength, electrical breakdown strength and other properties of the aramid paper.

[0153] It should be noted that, although the technical solutions of the present invention are described with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0154] While various embodiments of the present invention have been described above, the above descriptions are intended to be illustrative, non-exhaustive, and not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is selected to best explain the principles of the embodiments, their practical applications, or technological improvements in the marketplace, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing composite aramid paper, characterized in that: The following steps are involved: Preparation of heterocyclic aramid stock solution: p-phenylenediamine, diamine monomer containing heterocyclic structure and terephthaloyl chloride are mixed in a solvent for polymerization to obtain heterocyclic aramid stock solution; Preparation of heterocyclic aramid nanofibers: diluting the heterocyclic aramid stock solution with a solvent, mixing with a poor solvent, stirring, shearing, dispersing, and washing to obtain heterocyclic aramid nanofibers; Preparation of mixed slurry: mixing the para-aramid fiber and the heterocyclic aramid fiber nanofibers and beating the mixed slurry; Papermaking of composite aramid paper: the mixed slurry is papermade to obtain composite aramid paper.

2. The preparation method according to claim 1, characterized in that: The heterocyclic diamine monomer includes 2-(4-aminophenyl)-5-aminobenzimidazole.

3. The preparation method according to claim 1 or 2, characterized in that: The ratio of the total molar amount of the p-phenylenediamine and the diamine monomer containing a heterocyclic structure to the molar amount of the terephthaloyl chloride is 1:1.001 to 1:1.007; and / or, The molar ratio of the p-phenylenediamine to the diamine monomer containing a heterocyclic structure is 3:7 to 8:2; and / or, The molar concentration of the terephthaloyl chloride is 0.1-0.3 mol / L.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the preparation of the heterocyclic aramid stock solution and the preparation of the heterocyclic aramid nanofiber, the solvent includes one or more of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The heterocyclic aramid stock solution also includes a co-solvent, and the co-solvent includes one or more of lithium chloride, calcium chloride, lithium bromide or calcium bromide; Preferably, the amount of the co-solvent added is 2-10% of the mass of the solvent.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In the preparation of the heterocyclic aramid nanofiber, the solvent is diluted by 5 to 20 times; and / or, The poor solvent includes one or more of water, methanol, ethanol, and tert-butanol.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the preparation of the mixed slurry, the basis weight of the paper is 20 to 150 g / m 2 and / or, The amount of the heterocyclic aramid nanofiber added is 20 to 150% of the total mass of the para-aramid; and / or, The para-aramid fiber includes para-aramid short fibers and para-aramid pulp; Preferably, the mass ratio of the para-aramid chopped fibers to the para-aramid pulp is 3:7 to 7:

3.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The mixed slurry also includes a dispersant, and the dispersant includes one or more of polyethylene oxide, polyacrylamide, and sodium alginate; Preferably, the added amount of the dispersant is 0.01-1% of the total mass of the para-aramid.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The papermaking process includes dehydration, drying and shaping, and high-temperature calendering treatment; Preferably, the dehydration comprises wire dehydration and press dehydration; and / or, The drying temperature is 60-200° C. and the drying time is 3-60 min; and / or, The temperature of the high temperature calendering treatment is 100-200° C., the pressure of the high temperature calendering treatment is 3-10 MPa, and the time of the high temperature calendering treatment is 1-10 min.

10. A composite aramid paper, characterized in that: The composite aramid paper is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • PPTA paper using aramid nanofiber for self-reinforcement and preparation method thereof

    CN108265566A

  • Aramid fiber-plant nanofiber composite aramid paper, preparation method and application thereof

    CN112553959A

  • High-dielectric para-aramid fiber paper and preparation method thereof

    CN109736138A

  • Preparation method of heterocyclic aramid paper

    CN111235943A

  • Method of manufacturing aramid copolymer and aramid fiber manufactured thereby

    KR1020140071669A

Cited By

  • Aromatic polyamide microfiber and composite paper thereof

    CN121110206A